Correlation between the diversity of vaginal microbiota and the risk of high-risk human papillomavirus infection. Issue 1 (January 2019) - Chao, Xiao-Pei; Sun, Ting-Ting; Wang, Shu; Fan, Qing-Bo; Shi, Hong-Hui; Zhu, Lan; Lang, Jing-He
Abstract : Objectives: Since other genital infections enhance HIV susceptibility by inducing inflammation and evidence suggests that the vaginal microbiome plays a functional role in the persistence or regression of high-risk human papillomavirus (HPV) infections, we investigated the relationship between the composition of the vaginal microbiota and the risk of high-risk HPV infection. Methods: The study included 151 healthy women (65 HPV-positive and 86 HPV-negative) aged 20–65 at enrollment. Total genome DNA from samples was extracted using the hexadecyltrimethylammonium bromide (CTAB) CTAB method. The vaginal microbiota composition was determined by sequencing barcoded 16S rDNA gene fragments (V4) on Illumina HiSeq2500. Results: Of the 30 most abundant bacteria at the genus level, we found only six bacteria with a statistical difference between HPV-positive and HPV-negative women: Bacteroides, Acinetobacter, Faecalibacterium, Streptococcus, Finegoldia, and Moryella. Lactobacillus was the predominant genus and was detected in all women, but there was no significant difference between the two groups for L. iners, L. jensenii, and L. gasseri . Furthermore, we found 26 types of bacteria with a statistical difference at the species level between the two groups. Anaerobic bacteria such as Bacteroides plebeius, Acinetobacter lwoffii, and Prevotella buccae were found significantly more frequently in HPV-positive women, which is the most important finding of our study. Conclusion: Our findings suggest a possible role for the composition of the vaginal microbiota as a modifier of high-risk HPV infection, and specific microbiota species may serve as sensors for changes in the cervical microenvironment associated with high-risk HPV infection. The exact molecular mechanism of the vaginal microbiota in the course of high-risk HPV infection and cervical neoplasia should be further explored. Future research should include intervention in the composition of the vaginal microbiota to reverse the course of high-risk HPV infection and the natural history of cervical neoplasia.